Pemberian Edukasi Mengenai Tablet Tambah Darah (TTD) Menggunakan Media Infografis dan Podcast Pada Siswi SMA X - Salsabila, Shafa; Kurniasari, Ratih (Jurnal Ilmiah Wahana Pendidikan, 2024)
Anemia is still an unsolved problem in Indonesia. The Indonesian government has held a supplementation program for Blood Added Tablet (BAT) for female students in junior high school and high school, unfortunately this program has not been maximized. Disobedience is one of the factors causing the program doesn’t run optimally. Providing education using supporting media is one of the efforts to increase the knowledge about BAT among female students. This education is provided online by distributing broadcast through the WhatsApp application to 40 female students in X High School. Participants will work on a questionnaire whose result will be processed using SPSS ver 25. The results of providing education usinginfographics and podcast have been proven to increase female student knowledge about BAT.